1977
DOI: 10.1111/j.1365-2125.1977.tb00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Age as a determinant of sensitivity to warfarin.

Abstract: 1 Parallel human and rat studies were carried out to confirm the previous suggestion of an increased sensitivity to warfarin in old age. 2 The anticoagulant response to warfarin was found to be greater in the elderly groups despite, in the case of the patient study, the elderly subjects being given a smaller weight‐related dose. 3 At the same plasma warfarin concentrations there was greater inhibition of vitamin K‐dependent clotting factor synthesis in the elderly. There was no difference in the rate of clotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(89 citation statements)
references
References 20 publications
4
84
1
Order By: Relevance
“…The phenomenon is not universal, however. Warfarin binding in plasma does not fall in the elderly, for example (Shepherd et al, 1977;Routledge et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon is not universal, however. Warfarin binding in plasma does not fall in the elderly, for example (Shepherd et al, 1977;Routledge et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…For some of them, for example age, the direction and the degree with which they interfere with the effects of oral anticoagulants has been determined with some precision (O'Malley et al, 1977;Husted & Andreasen, 1977;Shepherd et al, 1977;Routledge et al, 1979). Other factors such as sex and indication for treatment remain controversial and uncertain (O'Malley et al, 1977;Routledge et al, 1979;Arboix et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Shepherd, Hewick, Moreland & Stevenson (1977) showed that vitamin K dependent clotting factors were more effectively inhibited by warfarin in the elderly. Clotting factor degradation, however, did not change with age, neither did the pharmacokinetics of warfarin.…”
Section: Methodsmentioning
confidence: 99%